Dynamic Teams in OpenMP - Schönherr, Jan H.; Richling, Jan; Heiss, Hans-Ulrich (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2010)
While OpenMP conceptually allows to vary the degree of parallelism from one parallel region to the next in order to adapt to the system load, this might still be too coarse-grained in certain scenarios. Especially applications designed for parallelism may stay within one parallel region for a long time. This may lead either to an oversubscribed system where individual applications are not restricted in their degree of parallelism, or to an underutilized system, because individual applications are restricted to a too small degree of parallelism. In this paper, we tackle both problems by dynamically restricting the number of active threads within a parallel region without violating the OpenMP specification.